How Financial Literacy Moderate The Association Between Financial Technology and Mental Accounting on Investment Decision? - Fadilatur Romadhan; Wuryan Andayani; Arum Prastiwi (Postgraduate Program Merdeka University, 2024)
This study aims to examine the effect of financial technology and mental accounting on investment decisions in generations Y and Z and to examine financial literacy in moderating the effect of financial technology and mental accounting on investment decisions in generations Y and Z. The study population was students in the East Java region who were active in investment activities totaling 232 people. The research population is students in the East Java region who are actively engaged in investment activities totaling 232 people. The type of research used is survey research using non-probability sampling techniques with Purposive sampling method. Data analysis was carried out using the Structural Equation Model to test the conceptual relationship between variables. The results of this study indicate that financial technology and mental accounting have a significant effect on investment decisions in generation Y and Z. The results also show that financial literacy is not able to moderate the effect of financial technology and mental accounting on investment decisions in generations Y and Z. JEL Classification: G02, G11, G110 DOI: https://doi.org/10.26905/afr.v7i3.14382